Tadabbur al-Ḥadīts: Solusi Masalah Khilafiyah - Arifuddin Ahmad (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2015)
The Prophet’s sayings become the second source of Islamic teaching after the Qur’ān. However, some views that Ḥadīth also becomes a source of heat debates and differences. To solve this problem, some scholars bestow tadabbur al-Ḥadīth, which deeply examines a Ḥadīth from its meaning residing behind the text. In this respect, tadabbur al-Ḥadīth employs some methodological approaches like al-jam‘ wa al-tawfīq and al-jam‘ wa al-tarjīḥ as well.